Conjugate observations of quasiperiodic emissions by the Cluster, Van Allen Probes, and THEMIS spacecraft. Issue 8 (16th August 2016) - Němec, F.; Hospodarsky, G.; Pickett, J. S.; Santolík, O.; Kurth, W. S.; Kletzing, C.
Abstract: We present results of a detailed analysis of two electromagnetic wave events observed in the inner magnetosphere at frequencies of a few kilohertz, which exhibit a quasiperiodic (QP) time modulation of the wave intensity. The events were observed by the Cluster and Van Allen Probes spacecraft and in one event also by the THEMIS E spacecraft. The spacecraft were significantly separated in magnetic local time, demonstrating a huge azimuthal extent of the events. Geomagnetic conditions at the times of the observations were very quiet, and the events occurred inside the plasmasphere. The modulation period observed by the Van Allen Probes and THEMIS E spacecraft (duskside) was in both events about twice larger than the modulation period observed by the Cluster spacecraft (dawnside). Moreover, individual QP elements occur about 15 s earlier on THEMIS E than on Van Allen Probes, which might be related to a finite propagation speed of a modulating ULF wave. Key Points: Multispacecraft (Cluster, Van Allen Probes, and THEMIS) observations of quasiperiodic emissions Huge azimuthal extent of the events, noticeable time delay (about 15 s) between individual spacecraft Modulation period on the duskside about twice larger than on the dawnside